Empirical study of the underlying theoretical hypotheses in the balanced scorecard (BSC) model: further evidence from Bangladesh / Md Habib-Uz-Zaman Khan, Abdel K. Halabi and Md. Zakaria Masud - Uz-Zaman Khan, Md Habib; K. Halabi, Abdel; Masud, Md. Zakaria (Accounting Research Institute (ARI), 2010)
This paper examines the underlying hypotheses of the Balanced Scorecard (BSC) which states that improvements relating to customers, learning and growth and internal processes improve the financial performance of an organization. In designing current research, the study focused on leading manufacturing and service companies based in Bangladesh and involved a structured questionnaire supported by financial data extracted from financial reports over three years. The results show that the BSC perspectives are positively correlated with each other at a statistically significant level and in a sequential way. Results also evidence that the companies that have improved their ROE and ROA had increased their efforts towards characteristics that involve the learning and growth perspective.